Peran Pesantren dalam Membangun Generasi Tafaqquh Fiddin - Aziz, Asep Abdul; Budiyanti, Nurti; Suhartini, Andewi; Ahmad, Nurwadjah (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2021)
Pesantren Persatuan Islam 1-2 Bandung is one of the modern pesantren (Islamic school) that combines religious science and general science with the aim of building a generation of tafaqquh fiddin. This goal is highly expected in improving the nationâ€™s increasingly devastated generation. Understanding of religion becomes the main foundation in al-akhlÄq al-karÄ«mah. This research uses qualitative approach with case study method in Pesantren Persatuan Islam 1-2 Bandung. The results of the study illustrate that Pesantren Persatuan Islam 1-2 Bandung has a role as the center of education of the Persatuan Islam (Islamic Unity). Of course this daâ€˜wah activity is also closely related to social activities carried out in the Pesantren Persatuan Islam. This is evidenced by the existence of educational institutions at various levels, social activities through devotion to educators and learners through the PKKJ program, as well as daâ€˜wah activities through taâ€˜lim, dÄâ€˜Ä« and dÄâ€˜iyah, coaching, Saturday taâ€˜lÄ«m, and activities programmed by QAYIM of Pesantren Persatuan Islam. Thus, Pesantren Persatuan Islam 1-2 Bandung has the big role in making Indonesian Muslims into tafaqquh fiddin, in order to strengthen religious understanding that always return to the Qurâ€™Än and Sunnah as guidelines for human life.